Literature Analysis On The Influence Of Transformational Leadership On Employee Performance - Marhaendro Purno; I Nyoman Tri Sutaguna; Melkior Lukas; Abdul Haris; Hustianto Sudarwadi (Economics And Business Management Journal ( EBMJ ), 2025)
Transformational leadership is a leadership style that aims to inspire and motivate employees to exceed their initial performance expectations. This leadership approach has been shown to have a positive impact on various aspects of employee performance, including productivity, work quality, attendance, creativity, and contribution to organizational goals. By fostering trust, admiration, loyalty, and respect, transformational leaders encourage employees to perform beyond standard expectations. Research indicates that transformational leadership positively influences employee performance, leading to increased self-confidence, commitment, and engagement in achieving organizational objectives. Additionally, transformational leaders are adept at developing employees' potential and strengthening the working relationship between leaders and subordinates.